Pro Kontra Penegakan Etik Secara Internal dan Eksternal - Angraini, Fauziah Suci (Jurnal Konstitusi & Demokrasi, 2021)
Ethical enforcement is starting to be seen as an important part of the norm system prevailing in society, whose it development cannot be separated from the existence of state institutions and professional organizations that demand public trust. Ethics has a direct contribution to the law enforcement, especially in monitoring the behavior of individuals by providing assurance to the public regarding the integrity of the behavior of law enforcers, public servants and professionals. The establishment of this ethical supervisory and enforcement agency can be found in various forms, it can be in the form of an inherent organ in the organization / institution that it supervises (internal) or that which stands as a separate institution (external). The debate began to emerge when the non-uniformity of the ethical supervisory institutions was considered to affect the procedures and quality of ethical enforcement itself. On the one hand, the internal enforcement of ethics is considered to be more protective of the dignity of individuals and organizations having ethical cases. But on the other hand, internal monitoring and enforcement of ethics has the potential to leave major questions from the aspect of ethics enforcers' independence. This problem is one of the fundamental question that must first be resolved in connection with the search for an ideal ethics enforcement supervisory institution format.